FYP Travel Agencies Website Application - Ooi , Li Juan (IRC, 2015)
There are more and more travellers in Malaysia nowadays, however the promotional of travel packages are limited on the travel agencies own website. So, the travellers choices are limited if they are surfing only few travel websites. The objective of this project is to design a website that enables the travel agencies and travellers to upload and view holiday destination tours. Functionality test is conducted with several circumstances to ensure the quality of the website. It is crucial to have a site to analyze and compare different holiday packages and ensure the purchase on the packages meet travellers need and expectation. To have better understanding of what the travellers wants on the site, the result is verified by quantitative survey. This survey reveals the expectation and background of the travellers to help the design of the travel platform. The results show that there are potential for the travel website to expand and provide more features and functionality. As summarizes from the result obtained from functionality test, it is clearly shown that the travel website can debug and run properly.